Muhammad Iqbal’s Politics of Spiritual Democracy - Dr Saad Malook, (Al Manhal Research Journal, 2024)
This article explains Muhammad Iqbal’s politics of spiritual democracy and examines its applications to Pakistan and the contemporary world. Almost an official doctrine has emerged that Pakistan's creation is the result of Iqbal’s philosophy. If it is the result of the intended or unintended consequences of Iqbal’s philosophy, the question is whether Pakistan has adopted the version of his democracy. Iqbal’s ‘spiritual democracy’ stands contrary to the European model of democracy. European democracy, according to Iqbal, is materialistic and acquires the interests of the individual rather than the interests of humanity. Iqbal used the expression “spiritual democracy” once in The Reconstruction of Religious Thought in Islam, he did not explain it. I interpret Iqbal’s ‘spiritual democracy’ in the holistic sense of Hegel’s idea of abstract-concrete distinction. I argue that Iqbal used ‘spiritual democracy,’ ‘Muslim democracy,’ and Islamic democracy, interchangeably in his writings. Drawing on the key values of Islamic ethics, notably freedom, equality, and fraternity, Iqbal developed his idea of spiritual democracy, which posits the idea of an ideal society by discarding racial, cultural, ethnic, or linguistic disparities for acquiring the common good. This article explains four theses of Iqbal’s moral and political philosophy to make sense of his model of spiritual democracy: first, human beings have the potential to legislate laws to make this world livable. Second, all human beings are equal in the moral sense. Third, human beings are free and responsible agents. Fourth, human beings have fraternal relationships to each other. So, the article explains the salient features of Iqbal’s politics of spiritual democracy and determines its implications for Pakistan, and the contemporary world.